Santé environnementale et État fédéral. Quelles stratégies d’acteurs sur l’action publique belge en matière d’ondes électromagnétiques ? - Caroline Deblander; Nathalie Schiffino (Développement Durable et Territoires, 2013)
International organizations encourage national regulation of environmental health (OMS, 1989 ; ONU, 1992). Meanwhile, we notice that environmental health as a concept or as a policy instrument has not been diffused in Belgium. Leaning on a study of the regulation of electromagnetic fields (EMF), we show that environmental associations and political decision-makers can play on the fuzzy definition of health and environment in order to challenge the framing of some public problems. Given that the definition of these public problems results from a social construction, we address the following research question: how is it possible to explain that the agenda-setting of EMF change from a health definition to an environmental one ? What is the consequences of this new image of the public policy ?